Validating the City Region Food System Approach: Enacting Inclusive, Transformational City Region Food Systems - Alison Blay-Palmer (Sustainability, 2018)
This paper offers a critical assessment of the value and utility of the evolving City Region Food Systems (CRFS) approach to improve our insights into flows of resources—food, waste, people, and knowledge—from rural to peri-urban to urban and back again, and the policies and process needed to enable sustainability. This paper reflects on (1) CRFS merits compared to other approaches; (2) the operational potential of applying the CRFS approach to existing projects through case analysis; (3) how to make the CRFS approach more robust and ways to further operationalize the approach; and (4) the potential for the CRFS approach to address complex challenges including integrated governance, territorial development, metabolic flows, and climate change. The paper begins with the rationale for CRFS as both a conceptual framework and an integrative operational approach, as it helps to build increasingly coherent transformational food systems. CRFS is differentiated from existing approaches to understand the context and gaps in theory and practice. We then explore the strength of CRFS through the conceptual building blocks of ‘food systems’ and ‘city-regions’ as appropriate, or not, to address pressing complex challenges. As both a multi-stakeholder, sustainability-building approach and process, CRFS provides a collective voice for food actors across scales and could provide coherence across jurisdictions, policies, and scales, including the Milan Urban Food Policy Pact, the Sustainable Development Goals, the Habitat III New Urban Agenda, and the Conference of the Parties (COP) 21. CRFS responds directly to calls in the literature to provide a conceptual and practical framing for policy through wide engagement across sectors that enables the co-construction of a relevant policy frame that can be enacted through sufficiently integrated policies and programs that achieve increasingly sustainable food systems.